Securing dryland resources for multiple users - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Close to one billion people worldwide depend directly on drylands for their livelihoods. Because of their variable and erratic climate and political and economic marginalization, drylands have some of the highest rates of poverty, including the world's poorest women and men. Users of dryland resources — including pastoralists, sedentary farmers, hunter-gatherers, and refugees — need to be assured of appropriate and effective access to sustain their diverse livelihood strategies in their risky shared environments. Pastoral and sedentary production systems that coexist in drylands very often use common property arrangements to manage their access to and use of natural resources. However, despite their history of complementary interactions, pastoralists and sedentary farmers increasingly face conflicting claims over land and other natural resources. Past policy interventions and existing regulatory frameworks have not offered lasting solutions to problems relating to land tenure and resource access for multiple and differentiated drylands resource users. These users require flexibility of access; they adopt opportunistic strategies to cope with the uncertain conditions in which they operate.